ASSOCIATION OF QUALITY OF SLEEP WITH COGNITIVE DECLINE AMONG THE PATIENTS OF CHRONIC KIDNEY DISEASE UNDERGOING HAEMODIALYSIS - Zubair, Usama Bin; Butt, Batool (Journal of Ayub Medical College Abbottabad, 2017)
Background: This study was conducted to determine the association between the subjective quality of sleep and cognitive decline among the patients of chronic kidney disease (CKD) undergoing haemodialysis. Methods: In this cross-sectional study 106 patients of chronic kidney disease (CKD) undergoing haemodialysis at a tertiary care hospital in Rawalpindi, Pakistan were included in the final analysis. Cognitive decline was measured by British Columbia Cognitive Complaints Inventory (BC-CCI). Sleep quality was measured by using the Pittsburgh Sleep Quality Index (PSQI). Relationship of age, gender, marital status, education, occupation, BMI, duration of dialysis, dialysis count per week, family income, tobacco smoking and use of naswar was assessed with the cognitive decline. Results: Out of 106 patients screened through BC-CCI and PSQI, 13.1% had no cognitive decline while 86.9% had significant cognitive decline. Relationship between quality of sleep and cognitive decline was significant on binary logistic regression. Conclusion: This study showed significant relationship between the sleep quality and cognitive decline among the patients of CKD undergoing haemodialysis. The findings of our study also call for a greater degree of understanding of the physical and psychological state of patients of CKD undergoing haemodialysis. Keywords: sleep quality; Cognitive decline; Haemodialysis; PSQI; BC-CCI